Efeito das notícias relacionadas à ESG no retorno das ações das empresas que compõem o ISE: Uma análise com estudos de eventos e implicações para a regionalidade - Oliveira, Sonia de Fátima (2024)
i) Contextualization: The companies listed at ISE are those that have best ESG practices and that are concerned with corporate performance. Even so, these companies may also occasionally commit irresponsible practices, generating negative news in the media. Therefore, it is necessary to understand whether the stock returns of these companies are affected by their irresponsible behavior and rewarded for their responsible behavior. ii) Objective: The aim of this research is to analyze the effect of news related to ESG on the stock returns of companies listed on the ISE. iii) Methodology: To carry out the research, news about companies belonging to ISE’s portfolio published on the Valor Econômico newspaper website between 2018 and 2022 were collected. The final sample comprises 44 companies and 224 news related to Environment, 192 related to Governance and 157 related to the Social factor. Data analysis was carried out in two stages. The first was a qualitative stage with analysis and classification of news according to the tone (positive or negative) and the second was a quantitative stage, with Event Study. iv) Results: In relation to the Environmental factor, the results show a negative effect of the negative news. However, there is no significant effect in relation to positive news. Regarding the Social factor, it was identified a positive effect of positive news, but it was not identified a significative effect of negative news. The results also indicate that positive news related to Governance can have a positive effect on stock returns, while negative news about Governance has a negative effect on stock returns. v) Compliance of the research with the concentration area of the Postgraduate Program in Administration (Regionality and Management) and with the line of research (Organizational Management and Regionality): The research aims to analyze the effect of news related to ESG on stock returns of the companies listed on the ISE being, therefore, related to the Management field and, more specifically, to the Organizational Management/Finance area. With regard to regionality, the regional implications of the research for companies of Alto Paranaíba and Triângulo Mineiro are presented. vi) Impact and innovative character on intellectual production: This research presents analyzes on the effect of news related to ESG in the Brazilian market, expanding the universe of previous studies that deal with the topic. vii) Economic and social impact: In the economic sphere, this research contributes to companies and regulators by identifying how the market reacts to positive and negative news about ESG. By showing that the Brazilian market is attentive to this news and is pricing this news even in the short term, the research results can contribute to companies' decision-making. In the social sphere, the results of this study can encourage the adoption of ESG practices by organizations, contributing to society in a practical way. viii) Regional implications: The results of this investigation may have implications for the companies of Alto Paranaíba and Triângulo Mineiro. Considering the possible financial effects of ESG news published in local media, these companies can be incentivized to adopt ESG practices, benefiting their communities and their internal and external stakeholders. ix) Sustainable Development Goals met in the research: The research is related to the Sustainable Development Goals (SDGs) that are part of the United Nations (UN) 2030 Agenda. By identifying the effect that positive and negative news can have on stock returns, this work can add knowledge to promote investments in diversity programs, improved governance and socially and environmentally responsible practices. Therefore, this research is aligned with SDG 17, which aims to “strengthen the means of implementation and revitalize the global partnership for sustainable development” (Nações Unidas Brasil, Agenda 2030, 2015, p. 19).